Metal or nonmetal cooperation with a phenyl group: route to catalysis? a computational investigation - Ghatak, Kamalika; Mane, Manoj; Vanka, Kumar (ACS Catalysis, 2013)
Full quantum mechanical calculations demonstrate that cooperativity in the form of the activation of the M-C bond (M: transition metal or boron, C: the ipso carbon of the coordinated phenyl group) can lead to effective catalysis pathways. Calculations show that the presence of an aromatic bidentate ligand attached to a transition metal, or even a main group element, such as boron, can lead to effective catalysts for,a, range of important reactions, such as the dehydrogenation of ammonia borane and formic acid and the activation of the N-H, bond in aromatic amities. Moreover, it is shown that the design of tridentate pincer complexes with the aromatic group at a terminal end can lead to effective M-C cooperativity. As such, the current work introduces a new concept in cooperativity and bond activation chemistry.
Keywords: catalysis; Density functional theory; metal-ligand cooperativity; small molecule activation

From ``Cosmic Cooking'' to chemistry of the future: a collective dialogue on chemistry as a tribute to Prof. Sourav Pal. - Roy, Soumyajit; Krishnamurty, Sailaja; Schoefberger, Wolfgang (Frontiers in Chemistry, 2022)
Keywords: cosmic cooking; coupled cluster and density functional calculations; dialogue on chemistry; pincers porphyrinoids and oxometalates; small molecule activation; Theoretical chemistry

Evaluating the catalytic potential of Lithium-decorated graphene quantum dots for small molecule activation - Samudre, Nikhil S.; Tiwari, Rukminesh (Chemical Physics, 2025)
The search for effective catalysts in small molecule activation has intensified as industries seek efficient and costeffective solutions. Lithium (Li), known for its unique electronic properties, is of significant interest as a catalyst. However, its specific catalytic potential when anchored on graphene quantum dots (GQDs) has not been fully explored. This study investigates the catalytic potential of lithium (Li) adatoms on GQDs with various edge conformations (zigzag and armchair) and sizes (24 and 42 atoms). Using density functional theory (DFT), we examine the interactions of Li-decorated GQDs with small molecules such as H2, N2, CO, O2, and CO2. Our findings reveal that Li-GQD complexes exhibit optimal catalytic activity for all these molecules, based on binding energy, charge distribution, and bond length changes. The smallest GQD, coronene (24 carbon atoms), shows the most promising catalytic activity, providing experimental leads for synthesizing and testing efficient Li-anchored catalysts.
Keywords: Catalytic activity; Density functional theory; graphene quantum dots; Lithium adatom; small molecule activation